An induced melting entanglement electroactive hydrogel with myocardial repair performance, a preparation method and application thereof
Patent Information
- Application Number
- CN202611177731.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-08-05
AI Technical Summary
①、为了获得生物相容性和湿稳定性,PEDOT难以以伸展的构象结合至水凝胶分子骨架上,进而难以形成更连贯的导电通路,水凝胶的电导率不足,而较低导电性能的水凝胶不能较好适配天然心肌电导率,造成梗死部位的电传导性能不佳,不利于恢复整个心脏的机电耦联,最终不利于修复受损心肌
(1)氧化硫酸葡聚糖侧链上丰富的磺酸基团能够有效掺杂导电聚合物PEDOT,使导电聚合物沿着多糖分子聚合,制备得到的PEDOT:ODS复合物,该复合物水分散性良好,便于后续加工和各种水性应用场景。
Smart Images

Figure CN122682096B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of medical materials, specifically relating to a hydrogel that employs a "crosslinking-untangling" strategy, using oxidized dextran sulfate as an anchor point, covalently crosslinking to untangle the hydrophobic chains of PEDOT:ODS during hydrogel molding, uniformly fixing conductive components, forming a continuous conductive pathway, improving conductivity and matching the conductivity of natural myocardium to improve electrical conduction in the infarcted area, thereby repairing damaged myocardium, along with its preparation method and application. Background Technology
[0002] The unique signal transduction and electromechanical coupling properties of cardiomyocytes enable the rhythmic contraction and relaxation of the heart. When a myocardial infarction occurs, the insulating properties of the fibrotic tissue in the infarcted area lead to blockage of electrical signal transmission, resulting in poor overall cardiac contraction, arrhythmia, and even sudden death.
[0003] PEDOT-based conductive hydrogels used for synchronized implantation therapy can effectively match the conductive properties of healthy myocardial tissue, acting as a conductor to re-establish electrical signal coupling at the infarcted and devitalized site, maintaining electromechanical signal coupling and ensuring normal cardiac function. However, the trade-off between biocompatibility and high conductivity in PEDOT-based conductive hydrogels remains a challenge in this field, significantly limiting the application of high-performance conductive materials in implantable diagnostic and therapeutic procedures for electrically active tissues such as myocardium. While sulfation-modified natural macromolecules can serve as doping templates for PEDOT and address issues such as poor biocompatibility and poor wet stability associated with traditional polystyrene sulfonate (PSS) doping, [the text abruptly ends here].
[0004] However, the above-mentioned gel still has the following problems: ① In order to obtain biocompatibility and moisture stability, PEDOT is difficult to bind to the molecular backbone of hydrogel in an extended conformation, which makes it difficult to form a more coherent conductive pathway. The conductivity of the hydrogel is insufficient, and the hydrogel with low conductivity cannot be well adapted to the natural myocardial conductivity, resulting in poor electrical conduction performance at the infarct site, which is not conducive to restoring the electromechanical coupling of the whole heart, and ultimately not conducive to repairing the damaged myocardium.
[0005] ② Because PEDOT is difficult to bind to the hydrogel molecular backbone in an extended conformation, it not only has poor electrical conductivity, but also poor anti-swelling and mechanical properties of the hydrogel.
[0006] When hydrogels exhibit poor swelling resistance and mechanical properties, they are prone to excessive water absorption and swelling, leading to volume deformation and disruption of internal conductive pathways. Poor mechanical properties result in insufficient mechanical strength and toughness, making them susceptible to cracking, breakage, and structural collapse under the traction of the myocardium's periodic contraction and relaxation. This not only significantly weakens their electrical conductivity and disrupts their mechanical compatibility with natural myocardium but also shortens the effective duration of the material at the infarct site.
[0007] Therefore, there is an urgent need for a hydrogel, its preparation method, and its application that allows PEDOT to bind to the hydrogel molecular backbone in a more extended conformation to improve electrical conductivity, anti-swelling properties, and mechanical properties. Summary of the Invention
[0008] To address the aforementioned shortcomings of the prior art, this invention provides an induced untangling electroactive hydrogel with myocardial repair properties, its preparation method, and its application, thereby solving the above-mentioned technical problems.
[0009] To achieve the above-mentioned objectives, the technical solution adopted in this invention is as follows: a method for preparing an induced untangling electroactive hydrogel with myocardial repair properties, comprising the following steps: (1) Sodium periodate and sulfated polysaccharide molecules are mixed in a solvent to prepare oxidized sulfated polysaccharide; (2) PEDOT:oxidized sulfate polysaccharide, EDOT monomer, ammonium persulfate and ferrous sulfate were mixed in a solvent to prepare PEDOT:oxidized sulfate polysaccharide; (3) Dissolve PEDOT: oxidized sulfate polysaccharide and amino-containing macromolecules separately, mix the two solutions, and prepare PODS hydrogel.
[0010] Further, step (1) includes: mixing the sodium periodate and sulfated polysaccharide molecules in a solvent, reacting at 20-30°C in the dark for 20-30 hours, adding ethylene glycol to terminate the reaction, and then dialysis and freeze-drying to obtain oxidized sulfated polysaccharide.
[0011] Furthermore, in step (1), the reaction temperature is 25°C and the time is 24h.
[0012] Furthermore, in step (1), the sulfated polysaccharide molecule is dextran sulfate, and the solvent is water; the molar ratio of glucose units on the dextran sulfate to sodium periodate is 1:1-1:1.5.
[0013] Further, step (2) includes: mixing the oxidized sulfate polysaccharide, EDOT monomer, ammonium persulfate and ferrous sulfate in a solvent, reacting at 0-4℃ for 36-54h, and washing to obtain the PEDOT: oxidized sulfate polysaccharide complex.
[0014] Furthermore, in step (2), the reaction temperature is 0℃ and the reaction time is 48h.
[0015] Furthermore, in step (2), the solvent is water, the oxidized sulfate polysaccharide is oxidized sulfate dextran, and the ferrous sulfate is ferrous sulfate heptahydrate; The mass ratio of oxidized sulfated dextran:EDOT monomer:ammonium persulfate:ferrous sulfate heptahydrate is 100:100:200:3-100:200:300:3.
[0016] Furthermore, in step (3), the amino-containing macromolecule is gelatin, and the solvent is water; After mixing, the mass concentration of PEDOT: oxidized sulfate polysaccharide is 2%-4%, and the mass concentration of gelatin solution is 4%-8%.
[0017] Furthermore, in step (3), the mass concentration of PEDOT: oxidized sulfate polysaccharide is 4%, and the mass concentration of the gelatin solution is 8%.
[0018] This invention provides an induced untangling electroactive hydrogel with myocardial repair properties prepared by the above-described preparation method.
[0019] This invention provides the application of an induced untangling electroactive hydrogel with myocardial repair properties in the preparation of drugs or medical devices for the treatment of heart failure after myocardial infarction.
[0020] Furthermore, the hydrogel is applied to the site of myocardial infarction via injection.
[0021] The beneficial effects of this invention are as follows: (1) The abundant sulfonic acid groups on the side chain of oxidized sulfuric acid dextran can effectively dop the conductive polymer PEDOT, so that the conductive polymer polymerizes along the polysaccharide molecule to prepare the PEDOT:ODS complex. The complex has good water dispersibility, which is convenient for subsequent processing and various water-based application scenarios.
[0022] (2) Oxidized sulfuric acid dextran is a modified product of natural polysaccharide with good biocompatibility. The prepared PEDOT:ODS complex has a neutral pH value, which is more suitable as an in vivo implant material than the traditional acidic PSS doping system.
[0023] (3) Oxidized sulfate dextran not only serves as a biocompatible dopant for PEDOT, but its functionalized aldehyde group can also undergo a Schiff base reaction with the amino groups on gelatin molecules. The gelation conditions are mild, and the resulting hydrogel is injectable.
[0024] (4) During the cross-linking process of PEDOT:ODS and gelatin, the hydrophobic chain entanglement formed by PEDOT undergoes a conformational change under the action of covalent bonds. PEDOT binds to the molecular backbone of hydrogel in a more extended conformation, which forms a more coherent conductive pathway in the hydrogel entity, greatly improving the conductivity of the hydrogel. It can better match the natural myocardial conductivity, increase the electrical conduction performance of the infarct site, and help restore the electromechanical coupling of the whole heart, ultimately helping to repair the damaged myocardium.
[0025] (5) The PEDOT hydrophobic polymer is distributed in a more extended conformation on the hydrogel backbone, which not only improves the conductivity, but also improves the swelling resistance and mechanical properties of the hydrogel.
[0026] In summary, the prepared hydrogel exhibits rapid gelation, good biocompatibility, and high conductivity. It effectively avoids the biotoxicity issues caused by the strong acidity of traditional PSS doping and solves the problem of discontinuous electrical signal transmission between core-shell conductive nanoparticles formed by conventional sulfated polysaccharide doping. It can establish a good electrical signal channel at the fibrotic site of myocardial infarction, adapt to the natural myocardial conductivity, enhance electrical conduction at the infarct site, thereby restoring the electromechanical coupling of the entire heart and further improving cardiac function from the perspective of electrophysiological reconstruction. Attached Figure Description
[0027] Figure 1 The water dispersibility and microstructure of PEDOT aqueous dispersions prepared in Example 1, Comparative Example 1, and Comparative Example 2 were studied. Figure 2 Skin tissue sections of rats on the third day and one month after intradermal implantation of the aqueous dispersions prepared in Example 1 and Comparative Example 1; Figure 3 The diagram shows the injectability properties of the hydrogel prepared in Example 1. Figure 4 (a) is a graph showing the shear thinning properties of the hydrogels prepared in Example 1, Comparative Example 1 and Comparative Example 2; Figure 4 (b) is a graph showing the change of storage modulus and loss modulus of the hydrogels prepared in Example 1, Comparative Example 1 and Comparative Example 2 with strain. Figure 5 The swelling curves of the hydrogels prepared in Example 1, Comparative Example 1, and Comparative Example 2 are shown. Figure 6 The conductivity diagrams are for the hydrogels prepared in Example 1, Comparative Example 1, and Comparative Example 2. Figure 7 Transient calcium behavior of primary neonatal rat cardiomyocytes on hydrogels prepared in Example 1, Comparative Example 1, and Comparative Example 2; Figure 8 Echocardiograms of rats with myocardial infarction on day 28 after treatment; Figure 9 The electrical conduction velocity spectra of each group of rats with myocardial infarction were obtained by in vitro electrophoresis on day 28 after treatment. Detailed Implementation
[0028] The specific embodiments of the present invention are described below to enable those skilled in the art to understand the present invention. However, it should be understood that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, various changes are obvious as long as they are within the spirit and scope of the present invention as defined and determined by the appended claims. All inventions utilizing the concept of the present invention are protected.
[0029] Unless otherwise specified, all raw materials used in the embodiments of the present invention are commercially available analytical grade materials.
[0030] Example 1 A method for preparing an electroactive hydrogel with myocardial repair properties that induces untangling and detangling, comprising the following steps: Step 1: Synthesis of oxidized sulfated dextran (ODS).
[0031] 1000 mg of dextran sulfate (DSS) was dissolved in 50 mL of deionized water. Based on the average molar mass of glucose units on the dextran sulfate (396.6 g / mol), the mass of NaIO4 at a molar ratio of 1:1.2 was calculated to be 640 mg. NaIO4 was dissolved in a small amount of water and then mixed with the DSS solution. The reaction was carried out in the dark at 25 °C for 24 h, and the reaction was terminated by adding 2 mL of ethylene glycol. The mixed solution was dialyzed against water for 3 days, and then lyophilized to obtain ODS.
[0032] Step 2: Synthesis of PEDOT:ODS aqueous dispersion.
[0033] 1000 mg ODS was dissolved in 50 mL of water under a stirring speed of 250 rpm. 900 μL of LEDOT (equivalent to 1206 mg of EDOT) with a density of 1.34 g / mL was added dropwise to the solution, while the reaction system was kept in an ice bath. After the system was thoroughly mixed, 2160 mg of ammonium persulfate and 30 mg of FeSO4·7H2O were added. The polymerization reaction was carried out at 0 °C for 48 h. Next, the dispersion was ultrasonically washed three times with deionized water to obtain the final PEDOT:ODS.
[0034] Step 3: Cross-linking to generate PODS hydrogel.
[0035] 36 mg PEDOT:ODS was dissolved in 300 μL of deionized water, and 72 mg of gelatin was dissolved in 600 μL of deionized water. The two solutions were mixed (the mass concentration of PEDOT:ODS after mixing was 36 mg / 900 mg, which equals 4%, and the mass concentration of gelatin was 72 mg / 900 mg, which equals 8%), and crosslinked to form a hydrogel PODS under gentle stirring.
[0036] Example 2 The difference between Example 2 and Example 1 is that in step one, the molar ratio of glucose units on dextran sulfate to NaIO4 is 1:1.5, and the mass of NaIO4 is 809 mg; in step two, the volume of EDOT added is 1400 μL; in step three, 40 mg PEDOT:ODS is dissolved in 200 μL of deionized water, and 80 mg of gelatin is dissolved in 800 μL of deionized water. The two solutions are mixed and crosslinked into hydrogel PODS under gentle stirring.
[0037] Example 3 The difference between Example 3 and Example 1 is that the molar ratio of glucose units on the dextran sulfate to NaIO4 is 1:1, and the mass of NaIO4 is 539 mg.
[0038] Comparative Example 1: The preparation of PEDOT:PSS-based conductive hydrogels includes the following steps: Step 1: Synthesis of oxidized dextran (ODex).
[0039] 1000 mg of dextran (Dex) was dissolved in 50 mL of deionized water. Based on the glucose units on the dextran, the mass of NaIO4 at a molar ratio of 1:1.2 was calculated to be approximately 1500 mg. NaIO4 was dissolved in a small amount of water and then mixed with DSS solution. The reaction was carried out in the dark at 25°C for 24 h, and the reaction was terminated by adding 2 mL of ethylene glycol. The mixed solution was dialyzed against water for 3 days, and then lyophilized to obtain ODex.
[0040] Step 2: Synthesis of PEDOT:PSS aqueous dispersion.
[0041] 1000 mg PSS was dissolved in 50 mL of water, and the mixture was stirred at 250 rpm. 900 μL of LEDOT was added dropwise to the solution, and the reaction mixture was kept in an ice bath. After the mixture was homogeneous, 2160 mg of ammonium persulfate and 30 mg of FeSO4·7H2O were added. The polymerization reaction was carried out at 0 °C for 48 h. Next, the dispersion was ultrasonically washed three times with deionized water to obtain the final PEDOT:PSS.
[0042] Step 3: Cross-linking to generate PPSS hydrogel.
[0043] 36 mg ODex and 36 mg PEDOT:PSS were dissolved in 300 μL of deionized water, and 72 mg gelatin was dissolved in 600 μL of deionized water. The two solutions were mixed and crosslinked into hydrogel PPSS under gentle stirring.
[0044] Comparative Example 2: The preparation of PEDOT:DSS-based conductive hydrogels includes the following steps: Step 1: Synthesis of oxidized sulfate dextran (ODex).
[0045] 1000 mg of dextran (Dex) was dissolved in 50 mL of deionized water. Based on the glucose units on the dextran, the mass of NaIO4 at a molar ratio of 1:1.2 was calculated to be approximately 1500 mg. NaIO4 was dissolved in a small amount of water and then mixed with DSS solution. The reaction was carried out in the dark at 25°C for 24 h, and the reaction was terminated by adding 2 mL of ethylene glycol. The mixed solution was dialyzed against water for 3 days, and then lyophilized to obtain ODex.
[0046] Step 2: Synthesis of PEDOT:DSS aqueous dispersion.
[0047] 1000 mg DSS was dissolved in 50 mL of water, and the mixture was stirred at 250 rpm. 900 μL of LEDOT was added dropwise to the solution, and the reaction mixture was kept in an ice bath. After the mixture was homogeneous, 2160 mg of ammonium persulfate and 30 mg of FeSO4·7H2O were added. The polymerization reaction was carried out at 0 °C for 48 h. Next, the dispersion was ultrasonically washed three times with deionized water to obtain the final PEDOT:DSS.
[0048] Step 3: Cross-linking to generate PDSS hydrogel.
[0049] 36 mg ODex and 36 mg PEDOT:DSS were dissolved in 300 μL of deionized water, and 72 mg gelatin was dissolved in 600 μL of deionized water. The two solutions were mixed and crosslinked into hydrogel PDSS under gentle stirring.
[0050] The experimental analysis data are as follows: I. Water dispersibility The water dispersibility and microstructure of the PEDOT aqueous dispersions prepared in Example 1, Comparative Example 1, and Comparative Example 2 were observed by transmission electron microscopy.
[0051] Experimental results are as follows Figure 1 As shown in the figure, the results indicate that the PEDOT:ODS prepared by this invention exhibits a typical core-shell structure in aqueous solution and is well dispersed.
[0052] II. Biocompatibility The inflammation and degradation of the aqueous dispersions prepared in Example 1 and Comparative Example 1 were observed in skin tissue sections on the third day and one month after implantation by intradermal implantation in rats.
[0053] Experimental results are as follows Figure 2 As shown, after intradermal implantation of PEDOT:ODS prepared in this invention into rats, no obvious neutrophil infiltration was observed in the tissue surrounding the implantation site in the early stage (3 days), indicating no obvious inflammation. Furthermore, on day 28, it was observed that the dextran of PEDOT:ODS was enzymatically hydrolyzed in vivo, and the metabolite glucose unit was non-toxic. In contrast, PSS in Comparative Group 1 caused obvious inflammation in the early stage of implantation, and it could not be degraded in vivo.
[0054] III. Gel-forming properties and injectability The gelling properties of the hydrogel prepared in Example 1 were tested by needle injection.
[0055] Experimental results are as follows Figure 3As shown, the results indicate that the hydrogel prepared in Example 1 of this invention can be injected from a 29G needle, proving that the hydrogel prepared in this invention has good injectability.
[0056] IV. Mechanical properties, swelling resistance, and electrical conductivity The rheological properties of the hydrogels prepared in Example 1, Comparative Example 1, and Comparative Example 2 of this invention were tested using an MCR302 rheometer. Steady-state shear flow was conducted at 37°C using a double concentric cylindrical geometry with a 1mm gap. The shear rate was increased from 0 to 100 s. - ¹, its viscosity curve was determined. The oscillation frequency of the strain scan was 1 Hz, and the strain ranged from 0.1% to 1000%.
[0057] Experimental results are as follows Figure 4 As shown, the results indicate that the hydrogel prepared in Example 1 of this invention has good shear thinning ability and its storage modulus is higher than that of the hydrogel prepared in the comparative example.
[0058] The hydrogels prepared in Example 1, Comparative Example 1 and Comparative Example 2 of this invention were freeze-dried and then immersed in PBS solution. The swelling performance of the hydrogel samples under physiological conditions was characterized by recording the weight of the hydrogel samples at different time points.
[0059] Experimental results are as follows Figure 5 As shown, the results indicate that the extended conformation of the PEDOT hydrophobic conductive polymer on the hydrogel molecular backbone forms a hydrophobic barrier for the PODS hydrogel prepared in Example 1 of this invention, effectively limiting hydration and thus exhibiting excellent anti-swelling properties.
[0060] The resistivity of the hydrogels prepared in Example 1, Comparative Example 1, and Comparative Example 2 of this invention was determined using the four-probe method.
[0061] Experimental results are as follows Figure 6 As shown, the results indicate that, compared with Comparative Examples 1 and 2, the PODS hydrogel prepared in Example 1 of this invention has the highest conductivity, which can more effectively couple with myocardial electrophysiology, improve cardiac function, and avoid inducing arrhythmias.
[0062] V. Validation by in vitro cell experiments using hydrogels Primary neonatal rat cardiomyocytes were seeded onto the surface of hydrogels prepared in Example 1, Comparative Example 1, and Comparative Example 2 of this invention. One week later, intracellular calcium ion staining was performed to observe the calcium transient behavior of cardiomyocytes on different hydrogels.
[0063] Experimental results are as follows Figure 7As shown, the results indicate that the hydrogel PODS prepared in Example 1 of this invention has the best biocompatibility and the highest conductivity, and the ion conduction behavior of primary cardiomyocytes on the PODS hydrogel is more mature and stable.
[0064] VI. In vivo efficacy testing of hydrogels To investigate the effect of an inducible untangling electroactive hydrogel with myocardial repair properties on in vivo cardiac injury repair, a rat model of myocardial infarction was established by permanently ligating the left anterior descending artery. In the treatment group, after myocardial ischemia and whitening were observed in the rats after modeling, 30 μL of hydrogel was injected into two sites—the infarct center and the infarct margin—using a 27G needle. On day 28, ultrasound examination was performed on the successfully modeled myocardial infarction rats, and rat hearts were collected for pathological section staining and observation.
[0065] M-mode echocardiography results are as follows: Figure 8 As shown, compared with the untreated model group, the hydrogel PODS group prepared in Example 1 of this invention showed a significant improvement in ventricular wall systolic-diastolic motion; Masson staining results on day 28 are as follows. Figure 9 As shown, compared with the control group, the hydrogel group prepared in Example 1 of this invention has the highest ventricular wall thickness and the smallest scar area, indicating that the hydrogel prepared in Example 1 effectively reduces the scar area at the site of myocardial infarction and proves its good cardiac repair function.
Claims
1. A method for preparing an induced untangling electroactive hydrogel with myocardial repair properties, characterized in that, Includes the following steps: (1) Sodium periodate and sulfated polysaccharide molecules are mixed in a solvent to prepare oxidized sulfated polysaccharide; (2) PEDOT:oxidized sulfate polysaccharide, EDOT monomer, ammonium persulfate and ferrous sulfate were mixed in a solvent to prepare PEDOT:oxidized sulfate polysaccharide; (3) Dissolve PEDOT: oxidized sulfate polysaccharide and amino-containing macromolecules separately, mix the two solutions, and prepare PODS hydrogel.
2. The method for preparing the electroactive hydrogel with myocardial repair properties according to claim 1, characterized in that, Step (1) includes: The sodium periodate and sulfated polysaccharide molecules were mixed in a solvent and reacted at 20-30°C in the dark for 20-30 hours. The reaction was terminated by adding ethylene glycol. After dialysis and freeze-drying, oxidized sulfated polysaccharide was obtained.
3. The method for preparing the electroactive hydrogel with myocardial repair properties according to claim 2, characterized in that, The sulfated polysaccharide molecule is sulfated dextran, and the solvent is water; The molar ratio of glucose units on the dextran sulfate to sodium periodate is 1:1 to 1:1.
5.
4. The method for preparing the electroactive hydrogel with myocardial repair properties according to claim 1, characterized in that, Step (2) includes: The oxidized sulfate polysaccharide, EDOT monomer, ammonium persulfate and ferrous sulfate were mixed in a solvent and reacted at 0-4℃ for 36-54 h. After washing, the PEDOT:oxidized sulfate polysaccharide complex was obtained.
5. The method for preparing the electroactive hydrogel with myocardial repair properties according to claim 4, characterized in that, In step (2), the solvent is water, the oxidized sulfuric acid polysaccharide is oxidized sulfuric acid dextran, and the ferrous sulfate is ferrous sulfate heptahydrate; The mass ratio of oxidized sulfated dextran:EDOT monomer:ammonium persulfate:ferrous sulfate heptahydrate is 100:100:200:3-100:200:300:
3.
6. The method for preparing the electroactive hydrogel with myocardial repair properties according to claim 1, characterized in that, In step (3), the amino-containing macromolecule is gelatin, and the solvent is water; After mixing, the mass concentration of PEDOT: oxidized sulfate polysaccharide is 2%-4%, and the mass concentration of gelatin solution is 4%-8%.
7. An induced untangling electroactive hydrogel with myocardial repair properties is prepared by the preparation method according to any one of claims 1-6.
8. The use of the electroactive hydrogel with myocardial repair properties according to claim 7 in the preparation of drugs or medical devices for the treatment of heart failure after myocardial infarction.
9. The application according to claim 8, characterized in that, The hydrogel is applied to the site of myocardial infarction via injection.
Citation Information
Patent Citations
Injectable hydrogel with redox activity and electroactivity as well as preparation method and application of injectable hydrogel
CN119909007A
Preparation method of heart failure treatment hydrogel with tissue repair and electric signal conduction functions
CN120324675A